2020
DOI: 10.1073/pnas.1922189117
|View full text |Cite
|
Sign up to set email alerts
|

Defined microbiota transplant restores Th17/RORγt+regulatory T cell balance in mice colonized with inflammatory bowel disease microbiotas

Abstract: The building evidence for the contribution of microbiota to human disease has spurred an effort to develop therapies that target the gut microbiota. This is particularly evident in inflammatory bowel diseases (IBDs), where clinical trials of fecal microbiota transplantation have shown some efficacy. To aid the development of novel microbiota-targeted therapies and to better understand the biology underpinning such treatments, we have used gnotobiotic mice to model microbiota manipulations in the context of mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…Intestinal Th17 cells can be induced by specific microbes, including Escherichia coli and Bifidobacterium. Escherichia coli was positively correlated with the proportion of RORγt+ and IL-17A + Th17 cells in the colon, while the proportion of IL-17A + Th17 cells in the colon of mice lacking only Escherichia coli was significantly reduced ( 97 ). Bifidobacterium and Lactobacillus inhibited the expression of IL-6 and IL-17 while facilitating the protein synthesis of major tight junction proteins ( 98 ).…”
Section: Interaction Between Gut Microbiota and Immune Cells In Apmentioning
confidence: 99%
“…Intestinal Th17 cells can be induced by specific microbes, including Escherichia coli and Bifidobacterium. Escherichia coli was positively correlated with the proportion of RORγt+ and IL-17A + Th17 cells in the colon, while the proportion of IL-17A + Th17 cells in the colon of mice lacking only Escherichia coli was significantly reduced ( 97 ). Bifidobacterium and Lactobacillus inhibited the expression of IL-6 and IL-17 while facilitating the protein synthesis of major tight junction proteins ( 98 ).…”
Section: Interaction Between Gut Microbiota and Immune Cells In Apmentioning
confidence: 99%
“…A study indicated that zinc deficiency activates the IL-23/Th17 axis, aggravating experimental colitis in mice ( 48 ). In addition, in a model of colitis, the transplantation of defined microbial flora has been shown to restore the balance of Th17/Tregs ( 49 ). Moreover, studies have confirmed that both Compound Sophorae Decoction and Rhubarb Peony Decoction exert protective effects against DSS-induced colitis in mice, and the mechanisms are related to the regulation of the Th17/Treg balance ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…135 Some GM-derived metabolites, such as shortchain fatty acids (SCFAs), can also mediate bone homeostasis through Tregs/Th17 cells. 136 Although evidence for a direct correlation between the GM and bone loss secondary to diseases is sparse, some disorders, such as IBD 137 and diabetes, 138 are associated with Tregs/Th17 cell-mediated inflammation. Moreover, these diseases are often accompanied by alterations in GM composition.…”
Section: Th17 and Tregs Mediates Gut Microbiome/bone Metabolism Interactionsmentioning
confidence: 99%